Dedicated computer-aided detection software for automated 3D breast ultrasound: an efficient tool for the radiologist in supplemental screening of women with dense breasts - Zelst, Jan C.M. van; Tan, Tao; Clauser, Paola; Domingo, Angels; Dorrius, Monique D.; Drieling, Daniel; Golatta, Michael; Gras, Francisca; de Jong, Mathijn; Pijnappel, Ruud; Rutten, Matthieu J. C. M.; Karssemeijer, Nico; et al. (European radiology, 2018)
Objectives - To determine the effect of computer-aided-detection (CAD) software for automated breast ultrasound (ABUS) on reading time (RT) and performance in screening for breast cancer. - - Material and methods - Unilateral ABUS examinations of 120 women with dense breasts were randomly selected from a multi-institutional archive of cases including 30 malignant (20/30 mammography-occult), 30 benign, and 60 normal cases with histopathological verification or ≥ 2 years of negative follow-up. Eight radiologists read once with (CAD-ABUS) and once without CAD (ABUS) with > 8 weeks between reading sessions. Readers provided a BI-RADS score and a level of suspiciousness (0-100). RT, sensitivity, specificity, PPV and area under the curve (AUC) were compared. - - Results - Average RT was significantly shorter using CAD-ABUS (133.4 s/case, 95% CI 129.2-137.6) compared with ABUS (158.3 s/case, 95% CI 153.0-163.3) (p < 0.001). Sensitivity was 0.84 for CAD-ABUS (95% CI 0.79-0.89) and ABUS (95% CI 0.78-0.88) (p = 0.90). Three out of eight readers showed significantly higher specificity using CAD. Pooled specificity (0.71, 95% CI 0.68-0.75 vs. 0.67, 95% CI 0.64-0.70, p = 0.08) and PPV (0.50, 95% CI 0.45-0.55 vs. 0.44, 95% CI 0.39-0.49, p = 0.07) were higher in CAD-ABUS vs. ABUS, respectively, albeit not significantly. Pooled AUC for CAD-ABUS was comparable with ABUS (0.82 vs. 0.83, p = 0.53, respectively). - - Conclusion - CAD software for ABUS may decrease the time needed to screen for breast cancer without compromising the screening performance of radiologists. - - Key Points - • ABUS with CAD software may speed up reading time without compromising radiologists’ accuracy., - • CAD software for ABUS might prevent non-detection of malignant breast lesions by radiologists. - , - • Radiologists reading ABUS with CAD software might improve their specificity without losing sensitivity.